Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan Batik Busak Uwe - Sudarto S; Abd. Salam Arsyad Putra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effect of service quality and product quality on customer satisfaction at Batik Busak Uwe in North Kalimantan. Service quality and product quality are two important factors that can influence the level of customer satisfaction in the batik industry. The method used in this study is a quantitative approach with a survey design, in which data were collected using questionnaires distributed to customers of Batik Busak Uwe. The data analysis technique employed was multiple linear regression to examine the relationship between the independent variables (service quality and product quality) and the dependent variable (customer satisfaction). The results show that service quality and product quality significantly affect customer satisfaction. In particular, service quality has a greater influence on customer satisfaction than product quality. These findings indicate the importance for Batik Busak Uwe to continuously improve service quality and product quality in order to enhance customer satisfaction and loyalty.